Effect of Coarse Aggregate Treatment On Characteristics of Pumice and Scoria Lightweight Concretes - Suseno, Hendro (International Journal of Integrated Engineering, 2023)
This study presents an experimental investigation of lightweight concretes production using typical pumice as well as scoria from Kelud volcano, Indonesia as coarse aggregates. Three different treatments were evaluated to obtain an effective treatment method. Method A was a combination of preheating to the temperature of 100o C and soaking for 2 hours. Method B was a direct presoaking for 3 hours and Method C was a premixing with water in the concrete mixer for 10 minutes. These methods were based on the water content of lightweight coarse aggregates tested before. The results showed that Method A provided the highest water content compared to Methods B and C. Similarly, it also provided the most satisfying workability during concrete production. Moreover, all physical and mechanical characteristics of hardened concrete were not affected by the coarse aggregate treatment methods given. Therefore, Method A was considered an effective treatment method. Pumice and scoria lightweight concretes constituted the structural lightweight concrete with the density reduction of 24% and 21% so that they can reduce the self-weight of element structures. However, the chord modulus of elasticity, the splitting tensile strength as well as the modulus of rupture was lower than the normal concrete and must be considered throughout in the structural lightweight concrete design.